Production and Distribution of Durian (Durio Zibethinus Murr.) in Wonosalam, Jombang - Djuhari Djuhari; Siti Muslikah; Lia Rohmatul Maula; Rose Novita Sari Handoko (Indonesian Journal of Environment and Sustainable Development, 2021)
The pattern of durian planting in the community, in general, uses the agroforestry pattern so that in one area of land there is more than one annual crop cultivated (multiple cropping). However, there is no distribution data map and its production potential. Research on mapping and potential of durian production in Wonosalam district is needed as an effort to provide data-based and to develop durian crop farming. The purpose of this study is to map the distribution of plants and the potential for durian production in the Wonosalam sub-district, Jombang district. The research is descriptive with surveys, observation, and in-depth interview methods. Farmer respondents were taken by "purposive sampling" from 4 hamlets. Each hamlet was taken from 15-20 durian farmer respondents. The mapping of the distribution of durian plants was made using Principle Component Analysis (PCA) using the Past (Palaeontological statistic) version 3.14 open source. The results showed that the distribution of durian trees in Wonosalam village was found in the four hamlets studied, namely Sumber, Wonosalam, Notorejo, and Mangirejo. The highest population of durian trees is in the highest order in Sumber hamlet, followed by Mangirejo, Wonosalam, and the lowest is Notorejo. The most planted varieties are local varieties, Bido, other local seedlings, and Introduction varieties (Montong and Weasel King). Bido variety were found in all four hamlets, but the number of farmers who plant these varieties is a maximum of 5 people. Bido variety as a national superior variety needs to be developed and spread to farmers so that it does not become extinct. The total potential of plant population in Wonosalam village is only 0.75% (2,075 trees) out of 278,369 trees in Jombang district. Keywords: durian, distribution, mountains, conservation